Growth Response and Yield of Chrysanthemum Applied with Various Dosages of Compost Made from Chrysanthemum Harvest Waste and Leaf Litter - I Gusti Made Arjana; Ketut Agung Sudewa; A.A> Putri Risa Andriani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
As a national priority floriculture crop in Indonesia, the chrysanthemum has seen significant expansion across various production centers. Driven by rising aesthetic demands, it serves as a vital income stream for local farmers. However, most cultivation is managed by smallholders who face capital constraints and limited access to modern technology, often resulting in sub-standard yields. To address this, research into accessible, domestic technologies—specifically those utilizing local resources—is essential to enhance product quality and added value. Sustainable soil management through compost application offers a cost-effective solution for small-scale farmers to improve their welfare. This study evaluates the efficacy of recycling chrysanthemum harvest waste and leaf litter into organic fertilizer. The primary objective was to determine the optimal compost type and dosage to maximize productivity and flower quality under local environmental conditions. The research employed a greenhouse experiment using a Nested Design within a Randomized Complete Block Design (RCBD) with a factorial pattern. Statistical analysis revealed that: Raw Material Type: Had no significant effect on the observed growth variables, suggesting both chrysanthemum waste and leaf litter are equally viable bases for compost. Dosage: Within each material type, dosage had a significant to highly significant impact on all variables.. Chrysanthemum Waste Compost: A dose of 4 tons ha^-1 yielded the highest economic fresh weight at 53.40 g (a 17.70% increase over the control). Leaf Litter Compost: The highest yield occurred at 12 tons ha^-1, weighing 50.77 g (an 18.22% increase). Contribution to Sustainable Development Goalas (SDGs): SDG 1: No Poverty; SDG 8: Decent Work and Economic Growth; SDG 12: Responsible Consumption and Production; SDG 15: Life on Land